Improving the Rumen Molar Proportion of Glucogenic Volatile Fatty Acids with the Inclusion of Siam Weed (Chromolaena odorata) Meal in Pelleted Diet of Fattened Cattle - Mullik, M. L.; Dato, T. O. D.; Mulik, Y. M.; Oematan, G. (Tropical Animal Science Journal, 2024)
The objective of this metabolism study was to evaluate the efficacy of Siam weed (Chromolaena odorata) meal in pelleted diets for fattened cattle. Four 2-year-old Bali steers were assigned to four dietary treatments using a 4x4 Latin square experimental design. The treatments were pellets containing chromolaena meal at 10% (10COM), 20% (20COM), 30% (30COM), or 40% (40COM). The pellet was given at 2% liveweight (LW), and kume (Sorghum plumosum var. Timorense) grass hay was offered ad libitum. The diets were isonitrogenous (20%) and energy (11.5 MJ ME/kg DM). Dietary intake, digestibility, and rumen fermentation were the variables measured. The results showed that increasing chromolaena meal to 40% substantially decreased the nutrient intake. Dry matter intake decreased from 2.5% LW in the 10COM to 2.19% LW in the 40COM. Likewise, crude protein intake decreased from 749 g/d (10COM) to 661 g/d (40COM). On the contrary, digestibility, rumen pH, ammonia concentration (116–125 mg/dL), and volatile fatty acids were not affected. It might be concluded that chromolaena can be used as a protein source for ruminants, but at high levels of inclusion (40%) tends to reduce intake.